High-strength and high-conductivity Cu-Zr-Cr alloy and preparation method thereof
Patent Information
- Application Number
- CN202611099678.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]本发明目的在于克服现有技术中铜合金强度与导电率相互制约、高性能工艺复杂无法工业化量产、生产成本高、成品成型性差、仅单一依赖析出强化导致强度不足的技术缺陷,提供一种可工业化的高强高导Cu-Zr-Cr合金及其制备方法
[0026]1.突破工业化量产“双70”性能瓶颈,填补市场空白。现有工业化Cu-Cr-Zr系合金在导电率≥70%IACS时,抗拉强度普遍仅为450~580MPa,行业量产天花板长期停留在“双65”水平(650MPa/65%IACS),而“双70”级材料仅能通过真空熔炼、超声辅助等实验室特种工艺小批量制备,无法量产。本发明在完全不依赖贵金属添加和特种设备的前提下,通过成分精准调控与工艺耦合创新,使成品抗拉强度稳定达到700~760MPa、导电率70~74%IACS,首次实现“双70”级Cu-Zr-Cr合金依托常规非真空熔炼和普通轧制设备规模化量产,直接解决了高端手机支撑板、高压开关触头、新能源导电构件及AI算力散热部件对高性能铜合金批量稳定供应的迫切需求。
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of high-strength and high-conductivity copper alloy materials, specifically relating to an industrially achievable high-strength and high-conductivity Cu-Zr-Cr alloy and its preparation method. Background Technology
[0002] Cu-Cr-Zr alloys are currently the most widely used high-strength, high-conductivity copper alloys in industry, capable of achieving matrix strength and toughness through both precipitation strengthening and deformation strengthening. Current traditional cold rolling and aging processes primarily rely on the nano-precipitation strengthening effect of Cr and Zr elements, failing to effectively utilize the deformation strengthening mechanism. This results in a single strengthening method, a relatively low overall strength limit for the alloy, and a significant bottleneck in the "strength-conductivity" trade-off.
[0003] Traditional Cu-Cr-Zr alloys, prepared using conventional industrial casting, hot rolling, cold rolling, and aging processes, typically exhibit tensile strengths of only 450–580 MPa while maintaining a conductivity of 70% IACS or higher. This fails to meet the stringent requirements for high strength, deformation resistance, and high stability in precision mobile phone support structures, high-voltage switches, and high-end conductive components in new energy applications. Currently, industrially produced high-strength, high-conductivity copper alloys generally only achieve a "double 65" performance level of 650 MPa strength and 65% IACS conductivity, representing the performance ceiling of existing mass production processes. With the rapid development of industries such as high-end consumer electronics and new energy power, high-performance copper alloys with both tensile strength ≥700 MPa and conductivity ≥70% IACS ("double 70") have become a necessity. However, there is a complete lack of industrially mass-producible "double 70" level copper alloy products on the market. Existing technologies can only produce small batches of "double 70" samples through specialized laboratory processes, hindering large-scale industrial production.
[0004] To overcome strength bottlenecks, the industry commonly employs methods such as ultra-large cold deformation and alloying with precious metals like rare earth elements, silver, and cobalt. While this can slightly improve strength, it severely damages the electrical conductivity of the copper matrix, causing conductivity to drop below 60% IACS. Simultaneously, it significantly increases costs and leads to decreased plasticity and poor formability. Other technologies utilize special processes like vacuum induction melting and ultrasonic vibration-assisted melting. While these can optimize performance, their high complexity, demanding equipment requirements, and extremely high production barriers prevent large-scale industrial production.
[0005] In summary, current industrialized copper alloy production is limited to the "double 65" bottleneck, while high-end "double 70" materials can only be prepared in laboratories and generally suffer from problems such as strength-conductivity trade-offs, complex processes, high costs, and poor formability. Furthermore, traditional single-stage aging processes combined with conventional rolling processes easily lead to uneven precipitate sizes and a high proportion of coarse precipitates within the alloy, resulting in low upper strength limits, large batch performance fluctuations, and poor microstructural stability, making it difficult to meet the demands of stable industrial production and high-end mass applications. Therefore, developing a "double 70" grade high-strength, high-conductivity Cu-Zr-Cr alloy that uses ordinary non-vacuum melting equipment, has a simple process, can be mass-produced on a large scale, can simultaneously activate both precipitation strengthening and deformation strengthening mechanisms, and breaks through the "double 65" ceiling has significant engineering application and market promotion value. Summary of the Invention
[0006] The purpose of this invention is to overcome the technical shortcomings of existing copper alloys, such as the mutual constraint between strength and conductivity, complex high-performance processes that prevent industrial mass production, high production costs, poor formability of finished products, and insufficient strength due to reliance solely on precipitation strengthening. This invention provides an industrially achievable high-strength, high-conductivity Cu-Zr-Cr alloy and its preparation method. This alloy can be widely used in high-end applications such as precision heat dissipation structures for consumer electronics, high-voltage conductive systems for new energy vehicles, high-voltage power switches, 5G communication base stations, and AI computing power heat dissipation, solving the industry's core pain point of difficulty in simultaneously achieving "conductivity, strength, heat dissipation, and mass production."
[0007] This invention, without adding rare earth elements, silver, or other precious metals, utilizes a precise component ratio and a coupled process of hot rolling + large deformation cold rolling + staged double aging + residual deformation rolling, which can be achieved using conventional non-vacuum melting furnaces, walking beam furnaces, and ordinary rolling mills. This process requires no special precision equipment and enables stable mass production. The invention employs large deformation precision rolling before aging to introduce dislocations, providing nucleation sites for nanoprecipitates. Uniform precipitation strengthening is achieved through double aging. Subsequent residual deformation rolling after aging significantly increases the matrix dislocation density, allowing precipitation strengthening and deformation strengthening mechanisms to work synergistically, greatly enhancing the alloy's strength while maximizing the preservation of the copper matrix's high conductivity and heat dissipation performance. This results in a stable overall performance of tensile strength ≥700MPa and conductivity ≥70%IACS, filling the market gap for industrialized "double 70" grade high-strength, high-conductivity copper alloys.
[0008] To achieve the above objectives, the present invention adopts the following technical solution:
[0009] An industrially producible high-strength, high-conductivity Cu-Zr-Cr alloy, with the following chemical composition by mass percentage:
[0010] Cr: 0.15%~1.0%;
[0011] Zr: 0.03%~0.2%;
[0012] The balance is Cu and unavoidable impurities;
[0013] Total impurities content ≤0.03wt%;
[0014] Preferably, the Cr content is 0.15% to 0.80%, and the Zr content is 0.05% to 0.18%.
[0015] This invention does not add auxiliary strengthening elements such as Ag, rare earth, Co, and Ni. Instead, it relies on a precise binary ratio of Cr and Zr, combined with a special heat treatment-rolling coupling process, to achieve nanoscale dispersion precipitation strengthening, thus preserving the high conductivity of the copper matrix to the greatest extent.
[0016] The preparation method of the alloy includes the following steps:
[0017] Step S1, Non-vacuum melting and casting: A conventional air melting furnace with a covering agent is used for melting at a temperature of 1150-1250℃ and a casting temperature of 1130-1150℃. Cu is added first to melt, followed by CuCr master alloy and CuZr master alloy. After degassing and impurity removal, the mixture is cast into a uniform, dense alloy ingot without pores.
[0018] Step S2, Homogenization Annealing and Hot Rolling Quenching: The ingot is fed into a walking beam furnace and held at 960-1030℃ for 2-4 hours for homogenization annealing to eliminate casting dendrite segregation; then it is hot rolled at 850-900℃ with a total deformation of 88%-93% and immediately water quenched after hot rolling at a cooling rate of 1.7-2.0 m / s to obtain a supersaturated solid solution billet.
[0019] Step S3, initial rolling: Perform multiple cold rolling passes at room temperature, with the total cold deformation controlled at 88% to 93%, rolling the billet to the intermediate thickness, introducing a high-density dislocation network into the matrix, providing nucleation sites for subsequent aging precipitation, while retaining the deformation allowance for subsequent finishing rolling.
[0020] Step S4, Room temperature large deformation precision rolling: Continue room temperature multi-pass cold rolling, with the total cold deformation reaching 93% to 98%, and roll the billet to the target thickness to further increase the dislocation density and make the matrix reach a fully work-hardened state;
[0021] Step S5, graded dual aging treatment: The first aging is carried out at 440-470℃ for 6 hours to rapidly desolvate the supersaturated solid solution and precipitate a large number of nano-sized Cr and Zr strengthening phases; the second low-temperature stabilization aging is carried out at 360-390℃ for 4 hours to refine the size of the precipitated phases, eliminate residual internal stress, avoid over-aging and coarsening of the precipitated phases, and ensure high conductivity.
[0022] Step S6, Deformation Rolling with Residual Material: After aging, perform multi-pass cold rolling at room temperature, with the total deformation controlled between 38% and 65%. According to the parabolic work hardening law of alloys, this range can achieve the optimal deformation strengthening effect, while avoiding the risk of a sharp decrease in plasticity and cracking caused by excessive deformation.
[0023] Step S7, tension straightening: The rolled strip is tension straightened and cut to obtain the finished alloy strip.
[0024] Preferably, the finished alloy has a tensile strength of 700-760 MPa and a conductivity of 70-74% IACS.
[0025] The advantages and beneficial effects of this invention are as follows:
[0026] 1. Breaking through the bottleneck of "double 70" performance in industrial mass production and filling a market gap. Existing industrial Cu-Cr-Zr alloys, with a conductivity ≥70% IACS, generally have a tensile strength of only 450–580 MPa. The industry's mass production ceiling has long been stuck at the "double 65" level (650 MPa / 65% IACS), while "double 70" grade materials can only be prepared in small batches through special laboratory processes such as vacuum melting and ultrasonic assistance, making mass production impossible. This invention, without relying on precious metal additions or special equipment, achieves stable tensile strength of 700–760 MPa and conductivity of 70–74% IACS in the finished product through precise composition control and process coupling innovation. This is the first time that "double 70" grade Cu-Zr-Cr alloys have been mass-produced using conventional non-vacuum melting and ordinary rolling equipment, directly addressing the urgent need for a stable, large-scale supply of high-performance copper alloys for high-end mobile phone support plates, high-voltage switch contacts, new energy conductive components, and AI computing power heat dissipation components.
[0027] 2. This application employs a three-stage process: "large deformation before aging + graded double aging + residual deformation after aging," achieving synergistic enhancement of precipitation strengthening and deformation strengthening. Traditional processes rely solely on the single strengthening mechanism of precipitation during aging, resulting in limited strength improvement. This invention first performs 93%–98% ultra-large cold deformation before aging, introducing a high-density uniform dislocation network within the matrix, providing numerous preferential nucleation sites for nano-precipitates and significantly improving nucleation efficiency. Then, graded double aging (first stage: rapid desolvation and precipitation at 440–470℃; second stage: stabilization and refinement at 360–390℃) achieves ultra-fine and uniform distribution of the precipitates, maximizing the contribution of precipitation strengthening. After aging, a separate residual deformation rolling process is added, further significantly increasing dislocation density and introducing secondary deformation strengthening. The three processes work in synergy, fully superimposing the dual mechanisms of precipitation strengthening and deformation strengthening, fundamentally breaking the strength upper limit bottleneck of traditional single precipitation strengthening.
[0028] 3. Based on the parabolic work hardening law of alloys, the allowable deformation range (38%–65%) is precisely defined to achieve the optimal balance between strengthening gain and plasticity. This invention, through systematic study of alloy work hardening curves, found that: when the deformation is below 38%, dislocation density accumulation is insufficient, and the deformation strengthening effect is weak; within the deformation range of 38%–65%, the alloy strength steadily increases with increasing deformation, and the conductivity remains above 70% IACS, while the plasticity remains within the machinable range; when the deformation exceeds 65%, dislocation multiplication tends to saturate, dynamic recovery intensifies, there is no significant strength gain, and instead, excessive accumulation of defects leads to a decrease in conductivity and a sharp deterioration in plasticity, significantly increasing the risk of cracking in the finished product. This invention strictly limits the allowable deformation to this optimal window, ensuring both maximum deformation strengthening effect and good material formability and yield, enabling the alloy of this invention to exhibit excellent process adaptability in actual stamping, bending, and other secondary processing.
[0029] 4. Scientifically designed composition window, low cost, and strong industrial compatibility. This invention strictly limits Cr to 0.15%–1.0% and Zr to 0.03%–0.2%, abandoning the existing approach of relying on adding precious metals such as Ag, rare earth elements, Co, and Ni to improve strength. Below this range, the precipitation strengthening effect is severely insufficient (e.g., the strength of Comparative Example 1 is only 632 MPa); above this range, a large number of coarse precipitates are generated, severely damaging conductivity and plasticity (e.g., the conductivity of Comparative Example 2 is only 64.2% IACS). The composition design of this invention, without adding any precious metals, balances high strength, high conductivity, and excellent processability. Raw material costs are controllable, and the entire process does not require special equipment such as vacuum melting or ultrasonic assistance. It has strong process adaptability and can be directly used in large-scale continuous production with existing copper processing equipment.
[0030] 5. This invention follows the parabolic work hardening law of alloys, precisely limiting the total deformation amount of the rolling process to an optimal window of 38%–65%. When the deformation amount is below 38%, the dislocation density accumulation is insufficient, and the deformation strengthening effect is weak. Within the deformation range of 38%–65%, the alloy strength steadily increases with the increase of deformation amount, and the conductivity remains above 70% IACS, while the plasticity remains within the machinable range. When the deformation amount exceeds 65%, dislocation multiplication tends to saturate, dynamic recovery intensifies, there is no significant gain in strength, and instead, the excessive accumulation of defects leads to a decrease in conductivity and a sharp deterioration in plasticity. This precise limitation achieves the best balance between strengthening gain and material plasticity, ensuring good formability of the finished product and industrial yield. Attached Figure Description
[0031] Figure 1 These are comparative metallographic images of alloys with different Cr contents according to the present invention; wherein, Figure 1 (a) is a metallographic image of an alloy with a Cr content of 0.4wt%, showing a uniform and dense structure without micron-sized coarse particles; Figure 1 (b) is a metallographic image of an alloy with a Cr content of 1.1 wt%, which shows a large number of micron-sized coarse Cr intermetallic compound particles and obvious structural defects. Detailed Implementation
[0032] The present invention will be further described in detail below through specific embodiments and comparative examples, but the implementation of the present invention is not limited thereto.
[0033] Examples 1-5
[0034] Alloy strips are prepared according to the following process flow:
[0035] Batching and Non-vacuum Melting: According to the chemical composition shown in Table 1, electric furnace melting is used. Electrolytic copper is added first, and after melting, CuCr master alloy and CuZr master alloy are added. The melting temperature is 1150-1250℃. Covering agent is used for protection. After degassing and impurity removal, casting is carried out at a casting temperature of 1130℃ to obtain ingots.
[0036] Sawing: Sawing the ingot cross-section to 170×320mm.
[0037] Homogenization annealing and hot rolling: The ingot is held at 960-1030℃ for 2-4 hours in a walking beam furnace, and then hot rolled with a pass rate of 20%-30% and a total processing rate of 88%-93%. The final rolled size is 15.5×350mm and the final rolling temperature is ≥760℃.
[0038] Quenching: Water quenching immediately after hot rolling, with a cooling rate of 1.7 to 2.0 m / s, to obtain a supersaturated solid solution billet.
[0039] Milling: The dimensions after milling are 12.6×330mm.
[0040] Room temperature large deformation precision rolling: multi-pass cold rolling reduces the thickness from 12.6 mm to 0.5 mm, with a total deformation of about 96%.
[0041] Graded dual aging: Level 1 aging at 440~470℃×6h, Level 2 aging at 360~390℃×4h, air cooling.
[0042] Deformation rolling with residual material: multi-pass cold rolling at room temperature, with the total deformation controlled according to Table 1.
[0043] Tension straightening: tension straightening and slitting to obtain finished strip material.
[0044] The component ratios and deformation amounts for each embodiment are shown in Table 1, and the performance test results are shown in Table 1.
[0045] Comparative Examples 1-4
[0046] The preparation processes of Comparative Examples 1 to 4 are the same as those of the Examples, except that the composition or the amount of deformation left is different, as shown in Table 1.
[0047] Performance testing methods: The room temperature tensile test was conducted on an electronic universal testing machine according to GB / T 228.1-2010, using a sheet metal specimen with a proportionality factor of 2.0 and a tensile speed of 1.5 mm / min. The conductivity was measured using an eddy current conductivity meter.
[0048] Test Results
[0049] Table 1. Component and performance test results of the examples and comparative examples.
[0050] Example 1 0.16 0.04 38% 702 72.8 Example 2 0.35 0.15 50% 725 71.2 Example 3 0.95 0.19 65% 753 70.1 Comparative Example 1 0.10 0.15 50% 632 73.5 Comparative Example 2 1.10 0.15 50% 685 64.2 Comparative Example 3 0.35 0.15 0% 578 71.5 Comparative Example 4 0.35 0.15 70% 728 69.8
[0051] The data in Table 1 will be analyzed below:
[0052] Comparative Example 1: The Cr content is only 0.10%, which is lower than the minimum design range of this invention. The matrix has insufficient Cr atoms in solid solution, the number of aging-precipitated nano-reinforcing phases is small, the precipitation reinforcement effect is seriously lacking, and the strength is supported only by deformation reinforcement. The final tensile strength is only 632 MPa, which cannot break through the industry's double 65 bottleneck and cannot meet the double 70 performance requirements.
[0053] Comparative Example 2: The Cr content of 1.10% exceeds the upper limit of the design of this invention. Excess Cr cannot be dissolved, generating a large number of micron-sized coarse and hard particles. Severe electron scattering causes the conductivity to plummet to 64.2% IACS. At the same time, it destroys the continuity of the matrix, significantly reduces the plasticity of the material, has poor formability, and the strength cannot meet the standard due to the uneven structure.
[0054] Comparative Example 3: The deformation rolling process after aging is omitted, and only a single precipitation strengthening mechanism is relied upon. There is no deformation strengthening superposition. The strengthening mechanism is single and the strength ceiling is low. The tensile strength is only 578MPa, which is far below the 700MPa standard.
[0055] Comparative Example 4: With a residual deformation of 70%, exceeding the optimal upper limit of 65%, dislocation multiplication in the alloy reaches saturation, resulting in no significant strength gain. Instead, excessive deformation leads to increased matrix defects, intensified electron scattering, a slight decrease in conductivity, and a significant deterioration in material plasticity, making the finished product prone to cracking and drastically reducing its industrial applicability. The above embodiments are merely illustrative of the technical solutions of the present invention and not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to depart from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An industrially producible high-strength, high-conductivity Cu-Zr-Cr alloy, characterized in that, The chemical composition, by mass percentage, is as follows: Cr:0.15%~1.0%; Zr:0.03%~0.2%; The balance consists of copper and unavoidable impurities, with a total impurity content ≤0.03 wt%. The Cu-Zr-Cr alloy does not contain any rare earth, silver, cobalt, nickel or other precious metal reinforcing elements. The alloy finished product has the following properties: tensile strength ≥700MPa, electrical conductivity ≥70%IACS.
2. An industrially scalable method for preparing a high-strength, high-conductivity Cu-Zr-Cr alloy, characterized in that, The method for preparing the Cu-Zr-Cr alloy according to claim 1 comprises the following steps: (1) Non-vacuum melting and ingot casting; (2) Homogenization annealing and hot rolling quenching; (3) Room temperature large deformation precision rolling; (4) Graded dual-time-effect treatment; (5) Deformation rolling with a blanking layer; (6) Stretch bending and straightening to obtain the finished alloy strip; In step (1), a conventional smelting furnace is used for smelting at a temperature of 1150-1250℃, and a covering agent is used for protective casting. Step (2) Homogenization temperature 960~1030℃, hold for 2~4h; hot rolling temperature 850~900℃, total hot rolling deformation 88%~93%, water quenching after hot rolling; Step (3) The total cold deformation of room temperature large deformation finishing rolling is 93% to 98%; Step (4) involves graded dual aging, including first-stage aging at 440–470℃ for 6 hours and second-stage low-temperature stabilization aging at 360–390℃ for 4 hours. Step (5) The total cold deformation of the rolling process is controlled at 38% to 65%.
3. The preparation method according to claim 2, characterized in that, The finished Cu-Zr-Cr alloy strip has a tensile strength of 700-760 MPa and a conductivity of 70-74% IACS.
4. The preparation method according to claim 2, characterized in that, The non-vacuum melting in step (1) is carried out in an electric furnace. First, Cu is added to melt, then CuCr master alloy and CuZr master alloy are added. After degassing and impurity removal, it is cast at a casting temperature of 1130-1150℃.
5. The preparation method according to claim 2, characterized in that, In step (2), the cooling rate of water quenching after hot rolling is 1.7 to 2.0 m / s to obtain a supersaturated solid solution billet.
6. The preparation method according to claim 2, characterized in that, In step (3), the room temperature large deformation finishing rolling is a multi-pass cold rolling, which reduces the thickness of the billet from 15.5 mm after hot rolling to 0.5 mm.
7. The preparation method according to claim 2, characterized in that, In step (5), the bottom deformation rolling is a multi-pass cold rolling at room temperature. The total deformation is controlled at 38% to 65% according to the alloy work hardening curve to avoid excessive deformation leading to plasticity deterioration.